The delimitation of “gross mistake” inside the jurisprudence of the General Accounting Office (Revista Digital de Direito Administrativo, 2020)
This present research is a study about the delimitation of “gross mistake” inside the jurisprudence of the General Accounting Office. Law 13.355/2018 includes in the Law of Introduction to the Norms of Brazilian Law (Decree-Law n. 4.657/1942) legal provisions about the efficiency at the creation and application of public law and provisions about legal safety, as the art. 28, which brought new definitions related to the accountability of the public agent. Through the inductive method with doctrine and General Accounting Office’s jurisprudence analysis, this research aims to approach the aspects related to control and investigation of responsibility towards this court, the recent changes to the LINDB with focus on the art. 28 and the application of these modifications at the jurisprudence of the General Accounting Office.